2019
DOI: 10.1186/s41182-019-0156-7
|View full text |Cite
|
Sign up to set email alerts
|

Modified Harada-Mori and simple wet mount to determine hookworm infections in Yo Island urban area, Songkhla, Southern Thailand

Abstract: Background Hookworm was a previously dominant parasitic infection in Southern Thailand. The changing population to an aging society in Yo Island has never been investigated for intestinal parasites. This study aimed to estimate the prevalence of hookworm and intestinal parasitic infections on Yo Island, a small island in Songkhla Province of southern Thailand. Methods A cross-sectional study was conducted among volunteers aged 15 and above to give one stool sample that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 14 publications
1
13
1
Order By: Relevance
“…The prevalence in this study was lower than those reported in other studies conducted in different regions of Thailand, including Chanthaburi Province (29.6%) and Surin Province (16.2%) [ 16 ]. In contrast, the overall prevalence in this study was higher than those in previous studies in Nakhon Si Thammarat Province (9.3%) and Songkhla Province (5.3%) [ 10 , 17 ]. The observed discrepancy might be due to differences in the climate, geographic location, age of the study population, sampling techniques, sociodemographic features and culture.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…The prevalence in this study was lower than those reported in other studies conducted in different regions of Thailand, including Chanthaburi Province (29.6%) and Surin Province (16.2%) [ 16 ]. In contrast, the overall prevalence in this study was higher than those in previous studies in Nakhon Si Thammarat Province (9.3%) and Songkhla Province (5.3%) [ 10 , 17 ]. The observed discrepancy might be due to differences in the climate, geographic location, age of the study population, sampling techniques, sociodemographic features and culture.…”
Section: Discussioncontrasting
confidence: 98%
“…Hookworms were the most predominant STH parasites, consistent with a previous study from China demonstrating that hookworms were the most prevalent in the elderly population [ 22 ]. In addition, the observed hookworm infection prevalence of 10.9% was higher than those in rural communities of Chachoengsao Province [ 15 ], Khon Kaen Province [ 23 ], Surin Province [ 16 ] and Songkhla Province [ 17 ]. In our study, the prevalence of hookworm infection in elderly individuals aged more than 80 years (19%) was higher than those in individuals aged 60–69 years (9.1%) and 70–79 years (11.3.4%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The specimen was kept for 10 days. 14 Afterwards, two parasitologists examined the plastic using microscope with 4 × magnification. Filariform larva was then identified morphologically by first putting the plastic on hot water to kill the larvae.…”
Section: Methodsmentioning
confidence: 99%